Internalisasi Nilai Hukum dan Syariat melalui Pendidikan Agama Islam sebagai Upaya Pencegahan Tindak Pidana Remaja - Khaerul Khaerul; Lilis Suryani; Andi Muhamamd Reza (Jurnal Litigasi Amsir, 2025)
This article examines the preventive role of Islamic Religious Education (PAI) in addressing the rising incidence of juvenile crime in Indonesia, such as theft, violence, and drug abuse among school-aged adolescents. Using a qualitative library research approach, the study analyses literature on adolescent psychosocial development, Islamic education, and crime prevention to map how family dynamics, school climate, peer interaction, and digital media exposure shape youths’ susceptibility to norm-violating and unlawful behaviour. It conceptualises PAI as an educational domain that integrates cognitive, affective, and spiritual dimensions by linking Qur’anic and Prophetic teachings on justice, responsibility, and self-control with contemporary challenges faced by adolescents in a globalised, media-saturated environment. Particular attention is given to the pedagogical role of PAI teachers as moral exemplars, the design of contextual and project-based learning that engages legal and ethical issues, and the creation of religiously supportive school cultures in synergy with parents and religious leaders. Through this framework, the article formulates concrete strategies for embedding anti-violence and anti-crime values into PAI curricula and practices, thereby positioning Islamic education as a key component within broader, collaborative efforts to strengthen youth character and legal awareness